Transformational Leadership Strategies and Innovative Leadership of Madrasah Principals in Improving Teacher Performance - Khoriroh, Fitri; Syarifudin, Encep; Apud, Apud (Halaqa: Islamic Education Journal, 2025)
Education plays a strategic role in shaping superior and competitive human resources. To achieve this goal, the leadership of the madrasah principal is crucial, not only as an administrator but also as a visionary leader capable of mobilizing and inspiring teachers as well as the entire school community. This study aims to analyze transformational and innovative leadership strategies implemented by principals of Madrasah Aliyah Negeri (MAN) in Cilegon City to improve teacher performance. The research employs a qualitative approach with a case study design conducted at MAN 1 and MAN 2 Cilegon. Data were collected through in-depth interviews, participant observation, and documentation review. The findings reveal that transformational leadership is manifested through a participatory long-term vision, inspirational motivation, teacher career development, planned change management, and effective communication and collaboration. Meanwhile, innovative leadership is reflected in openness to new ideas, creativity in problem-solving, adaptability to change, and teacher empowerment based on strong values and ethics. The implementation of both strategies has proven to enhance teachers’ pedagogical, professional, social, and personal competencies, while also encouraging active participation in continuous professional development. This study concludes that the combination of transformational and innovative leadership constitutes an effective strategy for creating a conducive work environment and improving the quality of education in madrasah. Highlights: Leadership practices combined long-term participatory vision with structured change management and ethical foundations. Open innovation systems and participatory decision-making supported continuous professional growth among educators. An integrated leadership framework emerged as a reference model for Islamic secondary education institutions. Keywords: Transformational Leadership, Innovative Leadership, Madrasah Teacher Performance